Spatial heterogeneity in the effect of regional trust on innovation - Thore Sören Bischoff; Petrik Runst; Kilian Bizer (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2023)
Previous studies have found that generalized trust positively affects innovation at the country and regional level. We extend this literature by arguing that there are four reasons to believe that the trust-innovation relationship is heterogeneous across geographic space. First, there is a saturation effect where regions in the lower half of the trust distribution are more likely to benefit from an increase in trust than regions in the upper half. Second, trust is more important in regions with less developed innovation capacities as it fosters cooperation and knowledge transfer, which is known to be especially relevant in lagging regions. Third, generalized trust and institutional trust can serve as substitutes: when institutional trust is low, generalized trust can be used as an alternative facilitator of cooperation. Finally, as smaller firms lack the legal capacities for sophisticated contractual arrangements and therefore resort to informal cooperation, the trust-innovation relationship is stronger in regions with a large share of small firms. Our results mostly support the small-firm and lower-trust region hypothesis. These findings underline the fact that regional innovation systems work differently and different mechanisms of cooperation can be leveraged to achieve innovation success depending on the regional characteristics.
Keywords: D02; D83; O12; O18; O31; 330; Innovation; trust; regional innovation systems